Resolution of the High versus Low debate for Old and Middle Kingdom Egypt - Pınar Erdil; Lyndelle Webster; Margot Kuitems; Christian Knoblauch; Laurel Bestock; Felix Höflmayer; Hans Beeckman; Dorian Q. Fuller; Sturt W. Manning; Michael W. Dee (PLoS ONE, 2025)
The unrivaled millennia-long historical chronology of ancient Egypt forms the backbone for archaeological synchronization across the entire Eastern Mediterranean region c. 3000-1000 BCE. However, for more than a century, scholars have wrangled over the correct calendrical positioning of this record, with older scenarios being referred to as ‘High’, and younger ones, ‘Low’ chronologies. Offsets between the two can be as great as a century, substantially confusing connections with other civilizations of the time. Here, we settle this debate for two major periods of political unity in ancient Egypt, the Old Kingdom (the Pyramid Age), and the Middle Kingdom. We introduce 48 high-precision radiocarbon dates obtained through rare access to museum collections as well as freshly excavated samples. By combining these new results with legacy radiocarbon data and with text records for reign lengths of kings within a Bayesian statistical framework, we show that the Low Chronology is no longer empirically supported for the Old and Middle Kingdoms, and resolve a long-standing historical schism.